2003
DOI: 10.1046/j.1365-2141.2003.04083.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein Ib polymorphisms influence platelet plug formation under high shear rates

Abstract: Summary. Platelet polymorphisms (Kozak, VNTR and HPA-2) within glycoprotein (GP)Iba may be associated with an increased risk of arterial thrombosis. However, the functional role of these polymorphisms has not been clarified. Their influence on platelet plug formation under high shear rates was, therefore, examined in 233 healthy individuals. Collagen-adrenaline-induced closure time was shorter in carriers of the C/D versus C/C VNTR allele and in homozygotes with the ()5)T/T versus ()5)C/T Kozak genotype as det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
2
4

Year Published

2004
2004
2007
2007

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 14 publications
3
19
2
4
Order By: Relevance
“…In yet another study of healthy young adults in Vienna, who were either HPA-2a (Thr,Thr) or HPA-2b (Thr, Met/Met,Met), platelet function testing indicated no significant difference in collagen/ epinephrine closure times, as measured by the PFA-100 TM assay. They also had similar expression of platelet surface GP Ib as measured by flow cytometric expression, indicating no platelet functional differences [21]. In our study that consisted of 22% African Americans, we found no significant differences in mean collagen/ADP closure times and comparable results with collagen/epinephrine closure when we compared results from those with Ko a (HPA-2b) and those with Ko b (HPA-2a).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In yet another study of healthy young adults in Vienna, who were either HPA-2a (Thr,Thr) or HPA-2b (Thr, Met/Met,Met), platelet function testing indicated no significant difference in collagen/ epinephrine closure times, as measured by the PFA-100 TM assay. They also had similar expression of platelet surface GP Ib as measured by flow cytometric expression, indicating no platelet functional differences [21]. In our study that consisted of 22% African Americans, we found no significant differences in mean collagen/ADP closure times and comparable results with collagen/epinephrine closure when we compared results from those with Ko a (HPA-2b) and those with Ko b (HPA-2a).…”
Section: Discussionsupporting
confidence: 53%
“…Furthermore, the presence of the C allele did not confer increased platelet aggregation in the entire group. Investigators have found that homozygotes with the -5TT Kozak genotype have shortened collagen-adrenaline-induced closure time when compared to those individuals who are -5CT [21]. However, others have not found an association between shortening of the PFA Collagen-epinephrine closure time and Kozak status [28].…”
Section: Kozak Polymorphismmentioning
confidence: 99%
“…As in population studies, results of platelet function studies for T145M variants are mixed (31)(32)(33)(34)(35)(36)(37)(38). No differences for variants were reported for ADP-induced platelet aggregation and von Willebrand factor binding (31), von Willebrand factor binding to truncated GPIb␣ T and M variant proteins (32), and collagen-epinephrine closure time (33).…”
Section: Discussionmentioning
confidence: 99%
“…No differences for variants were reported for ADP-induced platelet aggregation and von Willebrand factor binding (31), von Willebrand factor binding to truncated GPIb␣ T and M variant proteins (32), and collagen-epinephrine closure time (33). However, other studies do report differences, including greater inhibition of von Willebrand factormediated platelet agglutination by aurintricarboxylic acid (a von Willebrand factor antagonist) for M allele carriers, but no difference in prolongation of collagen-ADP closure time (34); increased ristocetin-induced and shear stressinduced agglutination and shortened collagen-epinephrine closure time for homozygous T subjects (35); greater binding of von Willebrand factor to T variant NH 2 -terminal fragments of GPIb␣-transfected Chinese hamster ovary (CHO) cells (36); mildly shortened collagen-ADP closure time for CAD patients homozygous for T (37); and, in CHO cell transfectants of T145M and a second GPIb␣ polymorphism (variable number tandem repeats) variants, stronger interaction of von Willebrand factor with the M variant of T145M (38).…”
Section: Discussionmentioning
confidence: 99%
“…All three characterized polymorphisms are located either in the promoter or in the coding region, which influence the amount of the receptor expression and/or its function [5,6,15,16]. Moreover, it is known that the distribution of the distinct alleles is heterogeneous among subjects of distinct ethnic backgrounds [8,12,14].…”
Section: Discussionmentioning
confidence: 99%